ANALISIS CSR DAN GCG TERHADAP KINERJA KEUANGAN DENGAN ISO STANDAR SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIS PADA PERUSAHAAN YANG LISTING DI LQ45) - Widia Wahyuningrum (BAJ: Behavioral Accounting Journal, 2019)
This study aims to test Corporate Social Responsibility and Good Corporate Governance on the company's financial performance, testing the effect of ISO on company performance. This type of research is quantitative research. Through this research the researcher tries to test the financial performance of the company that is listing in LQ 45 which is influenced by Corporate Social Responsibility, Good Corporate Governance, and ISO Standard 14001. The results showed that GCG had a significant effect on Tobins Q, so that it can be interpreted that companies that implement GCG can help companies improve their financial performance. CSR has no significant effect on Tobins Q. It can be interpreted that CSR focuses more on the problems that might arise on the external company and does not have a direct influence on financial performance. GCG has a significant effect on ISO, this can be interpreted when companies that implement GCG and are accompanied by obtaining ISO certification, will be able to help each other in creating good governance for the company. CSR has no significant effect on ISO. It can be interpreted that companies that implement CSR have no influence on the ISO certification that the company has. ISO has an effect on Tobins Q. It can be interpreted that companies that have ISO certification can have a positive effect on the company's financial performance.